The Association of Tobacco Smoking, Second-hand Smoke, and Novel Tobacco Products With COVID-19 Severity and Mortality in Italy: Results From the COSMO-IT Study - Silvano Gallus; Cristina Bosetti; Giuseppe Gorini; Chiara Stival; Roberto Boffi; Alessandra Lugo; Giulia Carreras; Chiara Veronese; Claudia Santucci; Roberta Pacifici; Biagio Tinghino; Vincenzo Zagà; et al. (Journal of Epidemiology, 2023)
Background: Despite the robust evidence of an excess risk of coronavirus disease 2019 (COVID-19) severity and mortality in ever smokers, the debate on the role of current and ex-smokers on COVID-19 progression remains open. Limited or no data are available on the link between electronic cigarette (e-cigarette), heated tobacco product (HTP) and second-hand smoke (SHS) exposure and COVID-19 progression. To fill this knowledge gap, we undertook the COvid19 and SMOking in ITaly (COSMO-IT) study. Methods: A multi-centre longitudinal study was conducted in 2020–2021 in 24 Italian hospitals on a total of 1,820 laboratory-confirmed COVID-19 patients. We estimated multivariable odds ratios (OR) and 95% confidence intervals (CI) to quantify the association between smoking-related behaviours (ie, smoking status, e-cigarette and HTP use, and SHS exposure) and COVID-19 severity (composite outcome: intubation, intensive care unit admission and death) and mortality. Results: Compared to never smokers, current smokers had an increased risk of COVID-19 mortality (OR 2.17; 95% CI, 1.06–4.41). E-cigarette use was non-significantly associated to an increased risk of COVID-19 severity (OR 1.60; 95% CI, 0.96–2.67). An increased risk of mortality was observed for exposure to SHS among non-smokers (OR 1.67; 95% CI, 1.04–2.68), the risk being particularly evident for exposures of ≥6 hours/day (OR 1.99; 95% CI, 1.15–3.44). Conclusion: This multicentric study from Italy shows a dismal COVID-19 progression in current smokers and, for the first time, in SHS exposed non-smokers. These data represent an additional reason to strengthen and enforce effective tobacco control measures and to support smokers in quitting.